Optimal Pension Design in General Equlibrium - Hans Fehr; Johannes Uhde (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The present paper aims to quantify efficiency properties of real world social security systems of various institutional designs in order to identify an optimal pension design. Starting from a benchmark economy without social security, we introduce alternative pension systems and compare the costs arising from liquidity constraints as well as labor and savings distortions versus the benefits from insurance provision against income and lifespan uncertainty. Our findings highlight strong efficiency losses arising from both means-testing pension benefits against private assets and restricting the contribution base while indicating a positive impact of means-testing flat benefits against earnings-related benefits within pension systems resting on several tiers. Furthermore, our results suggest that the negative correlation between pension progressivity and pension generosity may be justified on efficiency grounds. In our model a single-tier universal earnings-related pension system yields the highest efficiency gains dominating flat benefits as well as two-tier systems of any form.
Keywords: C68; H55; H31; 330